Kondisi Fisik Atlet Putra Cabang Olahraga Basket Surabaya Cambridge School - Hidayat, Wika Sufyan; Sulistyarto, Soni; Khuddus, Lutfhi Abdil; Fithroni, Hijrin (MAN Insan Cendekia Jambi, 2024)
This study aims to analyze the physical condition of male basketball athletes at Surabaya Cambridge School to evaluate their level of physical fitness based on various physical test parameters. The research used quantitative descriptive methods with 13 male athletes as subjects. Data collection was carried out through physical testing which included vertical jump, 20M sprint, push up, pull up, crunch, plank, lane test, medicine ball throw, and Vo2Max. The research results showed that the vertical jump was in the Medium category (46.2%), the 20M sprint was in the Poor category (76.9%), the push up were in the Good category (69.2%). Pull-ups below are very poor (69.2%). The crunch test was equally divided between the Good (46.2%) and Very Good (46.2%) categories, the plank was in the Good category (69.2%). Lane test in the Medium category (53.8%), medicine ball throw in the Fair category (53.8%). Vo2Max test in the Medium category (61.5%). These results concluded that the physical condition of Surabaya Cambridge School male basketball athletes was generally at a sufficient level. However, several aspects such as pull ups and medicine ball throws need more attention to improve the athlete's overall physical abilities. This research contributes to providing benchmarks for the development of athletes' physical fitness and recommendations for improving training programs that are more focused on physical aspects that are still less than optimal.